Evaluation of 2,2-diphenyl-1-picrylhydrazyl Scavenging Activity and Phytochemical Analysis of Mukia Maderaspatana (L.) M. Roem.: Evaluation of 2,2-diphenyl-1-picrylhydrazyl Scavenging Activity and Phytochemical Analysis of Mukia Maderaspatana (L.) M. Roem. - Arunprasath, A. (International Journal of Pharmaceutical & Biological Archive, 2018)
Mukia maderaspatana belongs to the family Cucurbitaceae is an important plant described in Ayurveda. This plant is used for the treatment of a number of ailments such as urinary disorder and cardiac problems. The leaf of M. maderaspatana was extracted with different organic solvents in increasing order of polarity. The results of the preliminary investigation revealed the presence of alkaloids, steroids, flavonoids, terpenoids, tannins, glycosides, and saponins. Antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The results of antioxidant activity indicate that the methanolic and petroleum ether extracts of the leaf of M. maderaspatana possess significant scavenging activity against DPPH (ethanolic solvent and methanolic solvent of 300 Î¼g/ml each). This study revealed that the methanolic extracts of M. maderaspatana have demonstrated significant antioxidant activity.